When is Grounded Theory (GT) Not Grounded Theory - Barry Chametzky (Grounded Theory Review: An International Journal)
The term grounded theory, in the vernacular sense, has a certain je-ne-sais-quoi; it sounds scholarly and is appealing to many researchers worldwide. Since its formal inception in 1967 with Glaser and Strauss the design has, for good or bad, undergone many modifications. However, the name has remained. To present the original design as grounded theory and modified versions of the design also as grounded theory seems awkward and confusing especially for students who are trying to learn the design. This confusion begs the question: When is grounded theory not grounded theory? In this paper, the author will present several methodological convergences and divergences in the design.